2023
DOI: 10.3390/diagnostics13101812
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Failure: An Evidence-Based Diagnostic Approach

Abstract: The diagnosis of adrenal insufficiency (AI) requires a high index of suspicion, detailed clinical assessment including detailed drug history, and appropriate laboratory evaluation. The clinical characteristics of adrenal insufficiency vary according to the cause, and the presentation may be myriad, e.g. insidious onset to a catastrophic adrenal crisis presenting with circulatory shock and coma. Secondary adrenal insufficiency (SAI) often presents with only glucocorticoid deficiency because aldosterone producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It is recommended to use a stimulation test to evaluate HPA function to diagnose CIRCI. However, studies have shown that the relationship between test results and patient outcomes is unclear, 22 while the risk of GI bleeding increases even after low dose of dexamethasone admission in the test. So the stimulation test should only do when CIRCI was highly suspected.…”
Section: Cortisol and Acth Level In Critical Illnessmentioning
confidence: 99%
“…It is recommended to use a stimulation test to evaluate HPA function to diagnose CIRCI. However, studies have shown that the relationship between test results and patient outcomes is unclear, 22 while the risk of GI bleeding increases even after low dose of dexamethasone admission in the test. So the stimulation test should only do when CIRCI was highly suspected.…”
Section: Cortisol and Acth Level In Critical Illnessmentioning
confidence: 99%
“…Negative results of the test with undetectable plasma cortisol suggested a secondary adrenal insufficiency in a 45-year-old male with bilateral foci of auricular ossifications (and negative endocrine autoimmunity) [ 28 ]. ACTH stimulation test remains a practical approach of the adrenal insufficiency diagnosis (including partial or latent forms) amid the presence of the rigid ears according to the general endocrine practice [ 59 , 60 , 61 , 62 , 63 ]. Another important issue included the evaluation of the metabolic features such as diabetes mellitus (four subjects within the endocrine cohort [ 1 , 21 , 34 , 38 ], but, also, two other patients in the non-endocrine cohort [ 46 , 50 ], had the condition, as well as one case of hypercholesterolemia [ 41 ]).…”
Section: Petrified Earsmentioning
confidence: 99%
“…Negative results of the test with undetectable plasma cortisol suggested a secondary adrenal insufficiency in a 45-year-old male with bilateral foci of auricular ossifications (and negative endocrine autoimmunity) [ 28 ]. ACTH stimulation test remains a practical approach of the adrenal insufficiency diagnosis (including partial or latent forms) amid the presence of the rigid ears according to the general endocrine practice [ 59 , 60 , 61 , 62 , 63 ].…”
Section: Petrified Earsmentioning
confidence: 99%

Hypopituitarism

Fleseriu,
Christ-Crain,
Langlois
et al. 2024
The Lancet